2018
DOI: 10.1002/berj.3468
|View full text |Cite
|
Sign up to set email alerts
|

Is exam hell the cause of high academic achievement in East Asia? The case of Japan and the case for transcending stereotypes

Abstract: High student achievement across East Asia is often explained as an outcome of highly competitive, stress‐inducing college entrance exams across the region. This ‘exam hell’ drives students to study longer and harder than their peers worldwide, a race that leads—unsurprisingly—to higher marks in international comparisons such as the Programme for International Student Assessment (PISA). Yet, the race comes at a considerable cost: psychological pressure, forfeited childhoods, regimes of rote memorisation, lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…However, we should be alert to a danger that, in an echo of the errors of the 'what works best' approach, findings will be used to make sweeping assertions about desirable educational practice without arriving at the more sensitive, contextualised understandings that are necessary for informing action. Indeed, without due consideration of ontological and epistemological foundations, even careful and sensitive attempts to introduce classroom approaches from other countries are unlikely to prove successful (Komatsu & Rappleye, 2018).…”
Section: The Promise Of Non-cognitive Factors In Large-scale Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we should be alert to a danger that, in an echo of the errors of the 'what works best' approach, findings will be used to make sweeping assertions about desirable educational practice without arriving at the more sensitive, contextualised understandings that are necessary for informing action. Indeed, without due consideration of ontological and epistemological foundations, even careful and sensitive attempts to introduce classroom approaches from other countries are unlikely to prove successful (Komatsu & Rappleye, 2018).…”
Section: The Promise Of Non-cognitive Factors In Large-scale Datasetsmentioning
confidence: 99%
“…While acting as a strong source of achievement motivation (e.g., Hau & Salili, 1996), and seemingly an important factor in the superior performance of Eastern Asian students (Leung, 2014), a negative consequence is it can result in overwhelming anxiety about the child's scholastic performance (e.g., Lee, 2009). Such pressures lead to undesirable psychological outcomes such as lack of enjoyment in learning, excessive stress, and undue preoccupation for, and fear of examinations [although with the positive changes driven by various countries such as Japan and China, we should be wary of stereotyping the Asian student's experience as being exclusively a joyless 'examination hell' (Komatsu & Rappleye, 2018)].…”
Section: National Examination Systems and The Emphasis On Meritocracymentioning
confidence: 99%
“…Evidence : in refutation of this, our analysis of PISA 2015 data suggests that Japanese 15 year olds spend less hours than their Anglo-American peers (Komatsu & Rappleye, 2018) and feel comparable exam-related anxiety (Rappleye & Komatsu, 2018). Qualitatively, the same results are obtained by an analysis of NIYE survey data (Komatsu & Rappleye, 2018). Moreover, no more than 20% of Japanese students attend cram schools at 10–12 grades when the competition becomes most severe during their school years (Rappleye & Komatsu, in press-a).…”
Section: Allowing Our Selves To Be Interruptedmentioning
confidence: 93%
“…Although its relevance has increased in US education, the role of PSE as an educational strategy among middle-class families is still limited. Recent studies of Japanese education have shown a significant decline over time of in-school and out-of-school learning times, and perceived pressure to study among Japanese students, which suggests declining relevance of PSE in Japan (Komatsu and Rappleye, 2018; Rappleye and Komatsu, 2018).…”
Section: Family Ses Academic Performance and Private Supplementary mentioning
confidence: 99%